Prenatal identification of a girl with a t(X;4)(p21;q35) translocation: molecular characterisation, paternal origin, and association with muscular dystrophy. Issue 7 (July 1990) - Bodrug, S E; Roberson, J R; Weiss, L; Ray, P N; Worton, R G; Van Dyke, D L
Abstract : There are 23 females known with Duchenne or Becker muscular dystrophy (DMD or BMD) who have X;autosome translocations that disrupt the X chromosome within band p21. A female with a t(X;4)(p21;q35) translocation was identified prenatally at routine amniocentesis. At birth, she was found to have a raised CK level, consistent with a diagnosis of Duchenne muscular dystrophy. Her cells were fused with mouse RAG cells and the translocated chromosomes were separated from one another and from the normal X chromosome by segregation in the resulting somatic cell hybrids. Southern blot analysis of the hybrids indicated that the translocation occurred on the X chromosome between genomic probes GMGX11 and J-66, both of which lie within the DMD gene. Further localisation with a subfragment of the DMD cDNA clone placed the translocation breakpoint in an intron towards the middle of the gene, confirming that the de novo translocation disrupted the DMD gene. RFLP analysis of the patient, her parents, and the hybrid cell lines showed that the translocation originated in the paternal genome. This brings to six out of six the number of DMD gene translocations of paternal origin, a fact that may be an important clue in future studies of the mechanism by which X;autosome translocations arise.